Investigating the role of women producers in alternative food networks implementing organic farming in Berlin Brandenburg - Darkhani, Faiza (Frontiers in Sustainable Food Systems, 2024)
This study sheds light on the challenges faced by women in alternative food networks (AFNs) applying organic farming in Berlin Brandenburg. They engage in AFNs as producers, consumers, and prosumers (producer-consumers). Literature indicates that individuals in farming face obstacles such as limited ownership, traditional gender roles, undervalued contributions, disparities in recognition and compensation, and barriers to leadership. The objective of this research is to understand the realities, self-perceptions, and conditions experienced by individuals in AFNs and organic farming. This study examines contextual factors, participation levels, decision-making processes, leadership dynamics, and impacts related to these participants. Using qualitative content analysis, interviews were conducted with active female respondents in three types of AFN: community-supported agriculture (CSA), food cooperatives (FCs), and self-harvest gardens (SHG). The interviewees expressed optimism about their involvement but emphasized the need for increased governmental support and community engagement. Participants in CSAs and FCs reported stronger producerconsumer connections and community building, while self-harvest gardeners sought personal growth and access to garden spaces. Interview data highlighted demands for gender equality improvements and support mechanisms. Addressing these challenges and promoting equal status for them can enhance their contributions to community building and localized food production. Recognizing their efforts fosters societal inclusiveness and progress.Understanding and supporting individuals in organic farming AFNs, we can move towards a future where their contributions are properly acknowledged.